2010
DOI: 10.3892/ijo_00000617
|View full text |Cite
|
Sign up to set email alerts
|

p57: A multifunctional protein in cancer (Review)

Abstract: Abstract. p57 is a cyclin-dependent kinase (CDK) inhibitor, the first cell cycle regulator that is regulated by imprinting. p57 was initially considered to be a tumor suppressor based on its ability to regulate cell cycle progression through its N-terminal domain. Now, it has been found that p57 is also involved in the regulation of other cellular processes including transcription, apoptosis, differentiation, development, and migration via its PAPA repeat and carboxyl-terminal domain. The multifunction of p57 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Overall, we identified a specific role for E47 in regulating Tbr1 + and Satb2 + projection neurons via p57(KIP2) during cortical development. Beside its function in brain development, p57(KIP2) has been implicated in adult NSC quiescence and neurogenesis (Furutachi et al, 2013(Furutachi et al, , 2015, cancer (Borriello et al, 2011;Guo et al, 2010), and human disorders (Duquesnes et al, 2016;John et al, 2001;Zhang et al, 1997). The Cdkn1c locus has been implicated in the Beckwith-Wiedemann syndrome, a growthregulation disorder characterized by tissue overgrowth and predisposition to tumors (Zhang et al, 1997), and mutations in different predicted enhancers have been suggested to contribute to the formation of the disease (Eggermann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we identified a specific role for E47 in regulating Tbr1 + and Satb2 + projection neurons via p57(KIP2) during cortical development. Beside its function in brain development, p57(KIP2) has been implicated in adult NSC quiescence and neurogenesis (Furutachi et al, 2013(Furutachi et al, , 2015, cancer (Borriello et al, 2011;Guo et al, 2010), and human disorders (Duquesnes et al, 2016;John et al, 2001;Zhang et al, 1997). The Cdkn1c locus has been implicated in the Beckwith-Wiedemann syndrome, a growthregulation disorder characterized by tissue overgrowth and predisposition to tumors (Zhang et al, 1997), and mutations in different predicted enhancers have been suggested to contribute to the formation of the disease (Eggermann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The result obtained in Lan-5 cells suggests that the Li-dependent p57 decrease was not correlated to N-Myc status ( Figure 2G). Usually, in immunoblotting analyses, p57 signal, as noted in Figure 2F,G, appears as a doublet where, as we recently demonstrated, the upper and slower migrating band corresponds to more phosphorylated isoform(s), while the lower band to hypo-or unphosphorylated form(s) [33]. Interestingly, beside the decrease of p57 total levels, the decline in the p57 upper band signal intensity was particularly evident ( Figure 2F,G), suggesting that Li affects p57 phosphorylation.…”
Section: Oxidative and Genotoxic Stress Determined By Licl Treatmentmentioning
confidence: 56%
“…Here we report the unprecedented observation that Li downregulates, in neuroblastoma cells, the p57 level by reducing CDKN1C transcription and also affects its post-translational modifications. p57 is a multifunctional protein involved in the control of growth, differentiation, gene expression, cytoskeletal organization, and apoptosis [24,33,37]. Recent pieces of evidence suggest that p57 plays a vital role in the maintenance of cellular homeostasis under stress conditions including those correlated with genotoxic response and activation of programmed cell death [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mutation/inactivation of CDKN1C in the cancer-susceptible Beckwith-Wiedemann syndrome also implied its importance in tumor suppression [37]. Now, it has been found that CDKN1C-encoded p57Kip2 is also involved in the regulation of various cellular processes such as transcription, differentiation, and migration through its PAPA repeat sequence and carboxy-terminal structural domain [32,33]. However, whether CDKN1C is also involved in the MDR of tumor cells, and its role and mechanism in the MDR of CRC cells remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…** p < 0.01; *** p < 0.001. P57Kip2 protein encoded by CDKN1C is a member of the Cip/Kip family of cyclindependent kinase inhibitors that acts as a cell cycle regulatory protein by binding to and inhibiting the activity of cyclin A/CDK2 and cyclin E/CDK2 complexes, thereby leading to cellular block in G1 phase and preventing DNA synthesis [32,33]. Thus, HCT8 cells may exhibit a stronger blocking effect in G1 phase.…”
Section: Mir-92b-3p Regulates the Sensitivity Of Hct8 And Hct8/t Cells To Chemotherapeutic Drugs By Targeting Cdkn1cmentioning
confidence: 99%